Environmental evidence of fossil fuel pollution in Laguna Chica de San Pedro lake sediments (Central Chile) - Chirinos, L.; Rose, N.L.; Urrutia, R.; Muñoz, P.; Torrejón, F.; Torres, L.; Cruces, F.; Araneda, A.; Zaror, C. (Elsevier, 2006)
This paper describes lake sediment spheroidal carbonaceous particle (SCP) profiles from Laguna Chica San Pedro, located in the Biobío Region, Chile (36° 51′ S, 73° 05′ W). The earliest presence of SCPs was found at 16 cm depth, corresponding to the 1915–1937 period, at the very onset of industrial activities in the study area. No SCPs were found at lower depths. SCP concentrations in Laguna Chica San Pedro lake sediments were directly related to local industrial activities. Moreover, no SCPs were found in Galletué lake (38° 41′ S, 71° 17.5′ W), a pristine high mountain water body used here as a reference site, suggesting that contribution from long distance atmospheric transport could be neglected, unlike published data from remote Northern Hemisphere lakes. These results are the first SCP sediment profiles from Chile, showing a direct relationship with fossil fuel consumption in the region. Cores were dated using the 210Pb technique.
Keywords: Airborne Pollution; Lake Sediment Dating; Biobío Region, Chile; https://purl.org/pe-repo/ocde/ford#1.05.11